Flow Blocks- Tangible Media - Lulu, Asma (2019)
Tangible media is a type of medium that interacts with the user via physical element controlled by digital data. Our project Flow Blocks is a tangible media table that could be used in educational, entertainment and architectural setting. As we know, everything is going smart in this century, so why still have static tables? Our dynamic smart table is not only to be up to date to the latest technologies and entertain people, but also to benefit them at the same time. Static tables are unhealthy; as it causes back pain to some people with limited movement disability, they will find it hard to grab items placed far or even read on a horizontal surface. “Flow Blocks” solve this problem by adjusting specific objects on the table. Flow Blocks has three main applications; performing a pre-programmed wave motion when clicking a button, interacting with the user hand motion and holding or moving objects placed on the table. The main element of the project is an elevating block, which is controlled by a linear actuator and a microcontroller. There are several sensors placed on the table and based on their values the blocks will interact with the user movement or environment. For example, if the user moved their hand over the table, the blocks will elevate their levels mimicking the user movement creating a wave. This will be done using ultrasonic sensors. If an object is place on the table, the sensors placed on the blocks would detect the object and based on the weight of the object different scenarios can occur; either the object is surrounded by blocks or the object is moved across the table. These sensors are force/pressure sensors. One major issue faced is arranging different sensory inputs and smoothing out the blocks movement by testing different codes and components that can be used to move the blocks. It is also noted that the table structure accommodates certain flows of electrical components used. While working on Flow Blocks, we found the potential and the variety of applications that can be used; also, the numerous ways of implementing a tangible media can create a new wave of interactive technologies. As for the future implementations and modifications, Flow Blocks will have additional functions and applications for luxury and fun.